Development Strategy of Ornamental Fish Cultivation Using The SWOT and QSPM Models: A Case Study of Betta Fish Cultivation Group Members in Kediri City - Hutami Putri Puspitasari; Agus Tjahjono (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
The main objective of this study is to analyze internal and external factors and recommend strategies for the development of betta fish cultivation. The method used is a descriptive qualitative method with case study techniques, while the selection of respondents uses a purposive sampling method through participatory observation with interviews based on questionnaires. Strengths, weaknesses, opportunities, and threats (SWOT) and quantitative strategic planning matrix (QSPM) analysis techniques are carried out to plan the required management strategies. The results showed that the IFE matrix analysis had a total score of 3.159 and EFE 2.835. In the SWOT matrix, allocating the betta fish cultivation business is located in quadrant I which can be interpreted as an aggressive growth (growth-oriented strategy) and on profitable growth. QSPM analysis results obtained top priority is to improve the quality and number of betta fish produced with a STAS value of 5.749. Based on this top priority, it can be used as input and reference consideration in making policies on betta fish cultivation business which includes strategic factors in the long term.